Inovasi dan Transformasi Digital dalam Meningkatkan Kualitas Pelayanan Publik di Bengkulu - Miyanda, Alga; Novliza Eka Patrisia; Susiyanto (JOPPAS: Journal of Public Policy and Administration Silampari, 2025)
This study aims to analyze the implementation of innovation and digital transformation in the delivery of public services in Bengkulu Province and its impact on service quality. The method used is a descriptive qualitative approach, with data collected through analysis of official government documents, observation of digital service platforms, and literature review. The results indicate that the adoption of digital services, such as online population administration, electronic licensing, digitalization of land and health services, and civil servant management, has improved efficiency, transparency, accessibility, and public satisfaction. However, the implementation of digital transformation is still constrained by several challenges, including limited infrastructure, low levels of digital literacy, fragmented service systems, and data security issues. In conclusion, digital transformation and public service innovation in Bengkulu Province have significant potential to enhance the quality of public services, but require strengthened infrastructure, data integration, improved human resource capacity, and sustainable digital governance to achieve optimal outcomes.   Keywords: Bengkulu, e-government, public service innovation, public service quality, digital transformation.